Regulation of UDP-Glucuronosyltransferase 1A1 Expression and Activity by MicroRNA 491-3p - Dluzen, Douglas F. (The American Society for Pharmacology and Experimental Therapeutics, 2014)
The UDP-glucuronosyltransferase (UGT) 1A enzymes are involved in the phase II metabolism of many important endogenous and exogenous compounds. The nine UGT1A isoforms exhibit high interindividual differences in expression, but their epigenetic regulation is not well understood. The purpose of the present study was to examine microRNA (miRNA) regulation of hepatic UGT1A enzymes and determine whether or not that regulation impacts enzymatic activity. In silico analysis identified miRNA 491-3p (miR-491-3p) as a potential regulator of the UGT1A gene family via binding to the shared UGT1A 3′-untranslated region common to all UGT1A enzymes. Transfection of miR-491-3p mimic into HuH-7 cells significantly repressed UGT1A1 (P < 0.001), UGT1A3 (P < 0.05), and UGT1A6 (P < 0.05) mRNA levels. For UGT1A1, this repression correlated with significantly reduced metabolism of raloxifene into raloxifene-6-glucuronide (ral-6-gluc; P < 0.01) and raloxifene-4′-glucuronide (ral-4′-gluc; P < 0.01). In HuH-7 cells with repressed miR-491-3p expression, there was a significant increase (∼80%; P < 0.01) in UGT1A1 mRNA and a corresponding increase in glucuronidation of raloxifene into ral-6-gluc (50%; P < 0.05) and ral-4′-gluc (22%; P < 0.01). Knockdown of endogenous miR-491-3p in HepG2 cells did not significantly alter UGT1A1 mRNA levels but did increase the formation of ral-6-gluc (50%; P < 0.05) and ral-4′-gluc (34%; P < 0.001). A significant inverse correlation between miR-491-3p expression and both UGT1A3 (P < 0.05) and UGT1A6 (P < 0.01) mRNA levels was observed in a panel of normal human liver specimens, with a significant (P < 0.05) increase in UGT1A3 and UGT1A6 mRNA levels observed in miR-491-3p nonexpressing versus expressing liver specimens. These results suggest that miR-491-3p is an important factor in regulating the expression of UGT1A enzymes in vivo.